Synthesis of 7,8-Dihydroxy-3-(3,4-dihydroxyphenyl)-2H-chromen-2-one Derivatives of Crown Ethers - (:unkn) unknown (WILEY, 2009)
The novel 1-(3,4-dimethoxyphenyl)-2-(2,3,4-trimethoxyphenyl)acrylonitrile was prepared from the condensation of the mixture of 2,3,4-trimethoxybenzaldehyde and 3,4-dimethoxyphenylacetonitrile in ethanol at 70 degrees C with 20% aqueous sodium hydroxide solution. Cyclization and demethylation of the acrylacetonitrile was performed using pyridine hydrochloride. The obtained 7,8-dihydroxy-3-(3,4-dihydroxyphenyl)-2H-chromen-2-one was reacted with the poly(ethylene glycol) ditosylates in CH3CN/alkali carbonate to afford bis-[12]crown-4, -[15]crown-5, and -[18]crown-6 chromenones. The chromatographically purified novel chromenone crown ethers were identified by IR, H-1 NMR, C-13 NMR, and MALDI-TOF mass spectrometry and elemental analysis.
Keywords: CATION-BINDING; COMPLEXATION